The effect of four weeks restricted diet on serum soluble leptin receptor levels and adipocyte leptin receptor density in normoweight rattus norvegicus strain Wistar (Medical Journal of Indonesia, 2006)
One of the five possible mechanisms of leptin resistance in human obesity is the defect in the leptin receptor (Ob-R). Evidence has accumulated that leptin-binding activity in human serum is related to a soluble form of the leptin receptor, and restriction of energy intake resulted a decrease in circulating leptin levels. Aim of this study is to examine the difference of serum soluble leptin receptor level and leptin receptor density in rat adipose tissue of adventitial aorta after four weeks treated with different restricted diets. Soluble leptin receptor level was measured by ELISA and leptin receptor density by using immuno-histochemistry. The soluble leptin receptor in group treated with 40% of normal daily calori diet was found significantly lower than control (p = 0.02). There were no any significant differences among group treated with 40 % of normal daily calori diet, â1 day fast-1day eatâ, and â1day fast-2 days eatâ groups, and among 1 day fast-1 day eatâ, âday fast - 2 days eatâ and control groups as well. On the other hand, leptin receptor density in adipose tissues was higher in restricted diet group than control. Diet of 40 % normal daily calorie for 4 weeks decreased soluble leptin receptor level, but increased adipocyte leptin receptor density of the adipose tissue of rat adventitial aorta. These changes may be resulted from an up regulation mechanism in relation with homeostatic maintenance. (Med J Indones 2006; 15:145-50) Keywords: restricted diet, leptin receptor, soluble leptin receptor, adipocyte, obesity